FORMES DE L’ABSENCE DANS LA CASA DE LOS ESPÍRITUS DE ISABEL ALLENDE. LE LIVRE ET LE FILM / FORMS OF ABSENCE IN ISABEL ALLENDE’S LA CASA DE LOS ESPÍRITUS. THE BOOK AND THE FILM - Diana-Adriana LEFTER; Lavinia GEAMBEI; Bogdan CIOABĂ (Incursiuni în imaginar)
The magical realism artistically defines Latin America. The literature of this cultural area is marked by the dual rootedness of the mentalities of this geographical area. Pure materiality versus diaphanous absence, telling silence versus muffled noise, clear contours versus dilution of forms are all ways of literary or cinematographic representation of this form of artistic manifestation called realismo magico. La Casa de Los Espíritus is Isabel Allende’s debut novel and a literary work in which the undeniable elements of magical realism are present both in the construction of the plot, in the creation of the characters and in the recurring themes specific to this literary movement. Isabel Allende’s novel tells the story of the Trueba family in Latin America over four generations, with a historical background from the early 20th century to the 1970s. The narrator’s narrative act is doubled by another defining narrative for Clara, the youngest daughter of the del Valle family: the diary she keeps assiduously until the day she dies. This diary becomes one of Clara’s “voices” when she chooses muteness as a form of expression of rebellion. Clara, Blanca and Alba - feminine names with an obvious symbolism, referring to light, to the diaphanous - are the female figures that represent the generations around which the story is articulated, while the figure of Nivea, representing the first generation, is less well defined in Allende’s novel. Also built around female figures is Billie August’s screenplay, with Clara’s almost obsessive presence beyond silence or death. The aim of our paper is to approach a unique subject reflected, with the respective tools, in two different arts. Starting from a literary text, La Casa de Los Espíritus, by Isabel Allende, and from the dramatization of the book, in Bille August’s directorial vision, released by Miramax in 1993, we want to detect, classify and analyse different types of forms of absence and the ways of constructing and representing it, in the literary text and in the cinematographic transposition. We consider that absence, through the establishment of a two-faced world - the spoken and the unspoken, the seen and the unseen, the material and the non-material, the solid and the vague - is the recurrent, strong and defining theme for the framing of these artistic productions belonging to the artistic current of the magic realism. Absence can be actualized, for example, in muteness and silence, in death, in escape into the imaginary. Marked negatively, absence, however, establishes a meaning, conveyed precisely through the absence of signal (auditory, visual, tactile). Literary and cinematographic resources for the representation of absence are obviously different, and our work aims to approach them in parallel, in order to observe similarities and differences in the process of production and reception.